Diastolic abnormalities in systemic sclerosis: evidence for associated defective cardiac functional reserve. Issue 7 (July 1996) - Valentini, G; Vitale, D F; Giunta, A; Maione, S; Gerundo, G; Arnese, M; Tirri, E; Pelaggi, N; Giacummo, A; Tirri, G; Condorelli, M
Abstract : OBJECTIVE: To investigate the pattern of diastolic abnormalities in patients with systemic sclerosis (SSc) and the relationship between impaired ventricular filling and systolic function. METHODS: Twenty four patients with SSc underwent M-mode and two dimensional echocardiography using echo-Doppler and gated blood pool cardiac angiography, both at rest and after exercise. RESULTS: An impaired diastolic relaxation of the left ventricle was detected in 10 of the 24 patients with SSc. Left ventricular ejection fraction at rest in these 10 patients with impaired ventricular filling did not differ from that in the remaining 14 patients, but eight of the 10 failed to increase their ejection fraction during exercise, compared with two of the 14 with normal ventricular filling (p = 0.003). CONCLUSION: Impaired relaxation of the left ventricle is a recently described feature of scleroderma heart disease. Diastolic dysfunction in SSc could depend on myocardial fibrosis or myocardial ischaemia, or both. It was found to be associated with a defective cardiac functional reserve. However, its prognostic significance remains to be clarified.